Flow-induced vibrations of a pitching and plunging airfoil. (25th February 2020) - Wang, Z.; Du, L.; Zhao, J.; Thompson, M. C.; Sun, X.
Abstract : Abstract : The flow-induced vibration (FIV) of an airfoil freely undergoing two-degrees-of-freedom (2-DOF) motions of plunging and pitching is numerically investigated as a function of the reduced velocity and pivot location in a two-dimensional free-stream flow. This investigation covers a wide parameter space spanning the flow reduced velocity range of $0<U^{\ast }=U/(\, f_{n}c)\leqslant 10$ and the pivot location range of $0\leqslant x\leqslant 1$, where $U$ is the free-stream velocity, $f_{n}$ is the natural frequency of the system set equal in the plunge and pitch directions, $c$ is the chord length of the foil and $x$ is the normalised distance of the pivot point from the leading edge. The numerical simulations were performed by employing an immersed boundary method at a low Reynolds number ( $Re=Uc/\unicode[STIX]{x1D708}=400$, with $\unicode[STIX]{x1D708}$ the kinematic viscosity of the fluid). Through detailed analyses of the dynamics of the 2-DOF vibrations and wake states, a variety of FIV response regimes are identified, including four regions showing synchronisation or near-synchronisation responses (labelled as S‐I, S‐II, S‐III and S‐IV) and four transition regimes (labelled as T‐I, T‐II, T‐III and T‐IV) that show intermittent, switching or chaotic responses, in the $x{-}U^{\ast }$ space.